Over-expression of FabA, FabB, and FabF from Photobacterium marinum J15 for enhancement of omega-7 monounsaturated fatty acid production in Escherichia coli - Moi, Ibrahim Musa (2018)
Omega-7 monounsaturated fatty acids comprising of palmitoleic acid (16:1ω7) and its elongation product cis-vaccenic acids (18:1ω7) are increasingly attracting scientific attention due to their multiple values in human health, industrial chemicals, and biodiesel formation. Conventionally, plants, animal fat products, vegetable and marine oil have been described to be the major sources of omega-7 fatty acids. However, all these natural sources provide a limited commercial quantity of these fatty acids. Besides, the chemical synthesis of these fatty acids bring about low efficiency and frequently requires harsh reaction conditions, prolonged times, and use of expensive equipments. Marine bacteria such as Photobacterium spp. contain omega-7 monounsaturated fatty acids in their membrane phospholipids which enable them to preserve their membrane fluidity. Considering the limited availability of these valuable fatty acids and other aforementioned problems associated with the other synthesis routes, developing metabolic strategies for enhancing the production of omega-7 fatty acids is of utmost importance. The main aim of this research was to enhance the production of omega-7 monounsaturated fatty acid in E. coli. In order to achieve that, fatty acids profile of P. marinum J15 and its biosynthesis pathway were determined. Three fatty acids genes designated as fabA, fabB, and fabF were amplified from P. marinum J15 genome. The genes were cloned and over-expressed individually and in combinatorial in E. coli BL21(DE3) to investigate their effects on the omega-7 fatty acids content. Effects of growth temperature on fatty acids content in recombinant E. coli were also studied. GC-MS analysis revealed the wild-type P. marinum J15 produced 51.6% of omega-7 fatty acids (36.3% of palmitoleic acid and 15.3% of vaccenic acid) after incubation at 20 °C. Fatty ac id biosynthesis pathway in P. marinum J15 contains 13 distinct proteins; 3 proteins (FabK, FabV, and FabY) are not commonly found in E. coli. Single over-expression of FabB in E. coli BL21(DE3) at 15 °C enhanced the omega-7 fatty acids by 3. 3 fold (53.9% of the total fatty acids). Meanwhile, single over-expression of FabA and FabF in E. coli BL21(DE3) enhanced omega-7 fatty acids only by 1.4 (23.1% of TFAs) and 1.6 (26.0% of TFAs) fold following incubation at 15 °C. Among the three genes, fabB showed the highest effect in the enhancement of omega-7 fatty acids, whereas fabA and fabF showed the lowest effect. Overexpression of fabA was important for increasing the amount of palmitic acids. Overexpression of the fabABF in E. coli BL21(DE3) enhanced the omega-7 fatty acids by 3.9 fold (70% of the total fatty acids) upon incubation at 20 °C. Incubation of the cells at lower growth temperature has been shown to increase the production of omega-7 fatty acids. In conclusion, this research may set the foundation for initiating new strategies to develop E. coli platforms devoted for large-scale production of omega-7 fatty acids.